2018
DOI: 10.1093/heapro/day028
|View full text |Cite
|
Sign up to set email alerts
|

eHealth and adolescents in Serbia: psychometric properties of eHeals questionnaire and contributing factors to better online health literacy

Abstract: Internet is important resource of health-related information and health services. Factors associated with higher level of online health (eHealth) literacy among adolescence have been understudied. The aim of this study was to assess psychometric properties of the eHealth Literacy Scale (eHEALS) in Serbian language and to evaluate eHealth literacy among adolescents in Serbia. The study was carried out in four high schools in Belgrade, Serbia in the period December 2016 to January 2017. A total of 702 students c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 23 publications
6
44
0
1
Order By: Relevance
“…The original assessment of the eHEALS carried out by Norman and Skinner [12] yielded a Cronbach’s alpha of 0.88. In other studies published to date, the Cronbach’s alpha ranged from 0.85 for the Serbian [57] to 0.93 for the Japanese [18] and the Dutch versions [15], and 0.95 for the Chinese version of the instrument [40]. Neter et al reported a Cronbach’s alpha coefficient of 0.86 for the six item version of the eHEALS scale [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The original assessment of the eHEALS carried out by Norman and Skinner [12] yielded a Cronbach’s alpha of 0.88. In other studies published to date, the Cronbach’s alpha ranged from 0.85 for the Serbian [57] to 0.93 for the Japanese [18] and the Dutch versions [15], and 0.95 for the Chinese version of the instrument [40]. Neter et al reported a Cronbach’s alpha coefficient of 0.86 for the six item version of the eHEALS scale [19].…”
Section: Discussionmentioning
confidence: 99%
“…It was also applied in surveys carried out on various groups of patients: recipients of ambulatory care [36,37], patients with chronic diseases [22,38,39,40,41], patients suffering from rheumatic diseases [15], human immunodeficiency virus (HIV) positive persons [42,43], primary lung cancer survivors [44], and parents of children with special health care needs [45,46]. Currently, there are also many national versions available, including German [47], Greek [48], Yidisz [19], Japanese [18], Dutch [15], Chinese [32,40], Korean [49], Turkish [50], Persian [35,51], Portuguese [33], Italian [52,53,54], Spanish [55,56], Arabic [31], and Serbian [57].…”
Section: Introductionmentioning
confidence: 99%
“…The eHEALS has been adapted to different languages in Asia [ 5 , 10 - 13 ] and Europe [ 14 - 18 ]. Furthermore, the psychometrics properties have been evaluated in different populations such as in students [ 4 , 12 , 15 , 19 , 20 ], adults [ 9 , 11 , 16 - 18 , 21 ], and patients with chronic diseases [ 5 , 14 , 22 , 23 ], as well as in different cultures in Australia [ 9 , 24 ] and North America [ 9 , 17 , 20 - 22 ]. The internal consistency reliability coefficient was shown to be acceptable (ranging from .80 to .90) in the majority of the linguistic versions of the eHEALS [ 4 , 11 - 13 , 15 - 19 , 23 ], indicating a reliable scale.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the psychometrics properties have been evaluated in different populations such as in students [ 4 , 12 , 15 , 19 , 20 ], adults [ 9 , 11 , 16 - 18 , 21 ], and patients with chronic diseases [ 5 , 14 , 22 , 23 ], as well as in different cultures in Australia [ 9 , 24 ] and North America [ 9 , 17 , 20 - 22 ]. The internal consistency reliability coefficient was shown to be acceptable (ranging from .80 to .90) in the majority of the linguistic versions of the eHEALS [ 4 , 11 - 13 , 15 - 19 , 23 ], indicating a reliable scale. According to construct validity, the majority of the studies supported a 1-factor model [ 5 , 10 , 12 - 14 , 16 , 22 , 23 , 25 ] recommended by the original scale [ 4 ], whereas a few other studies have recommended a 2-factor [ 11 , 15 , 18 ] or 3-factor [ 9 , 21 , 24 ] model.…”
Section: Introductionmentioning
confidence: 99%
“…Only in 1 study from Slovenia did we find the validation of an extended version of 20 items (6 factors) including the Web 2.0 parameter as discussed earlier by Norman [49,50]. In 21 cases, the authors preferred a combination of the original scale adding questions to assess health-related internet use and internet use in general [17,25,27-29,31,51-64]. The reliability in the majority of the studies was quite high, that is, over 0.80.…”
Section: Resultsmentioning
confidence: 99%